Comunicación interauricular - Rodríguez Vicencio, Gastón (1965)
Recently, cardiac surgery has been extended for the treatment of atrial septal defects ; Murray work ( 45 ) , Swan ( 60 ) , Bailey (6 ) , Gross ( 27 ) , Biork - Crofoord (10 ) , Kirklin ( 32 ) , Lewis ( 37 ) , Gibbon ( 25 ) and Lillehei ( 38 ) have demonstrated the successful closure of such defects is feasible in most cases , with a low percentage of mortality and targets with highly satisfactory results. The development of these techniques has once more the need and importance of early diagnosis and the most accurate of congenital cardiac malformations , as an essential first step for proper surgical treatment. Diagnosis of Septal and its various forms , differentiation between isolated and shapes . associates and complex shapes and an intimate knowledge of its natural history and prognosis , have now , therefore, a purely academic or theoretical but highly practical value.